"Touch microbiome" as a potential tool for forensic investigation: A pilot study. (August 2021) - Procopio, Noemi; Lovisolo, Flavia; Sguazzi, Giulia; Ghignone, Stefano; Voyron, Samuele; Migliario, Mario; Renò, Filippo; Sellitto, Federica; D'Angiolella, Gabriella; Tozzo, Pamela; Caenazzo, Luciana; Gino, Sarah
Abstract: Human skin hosts a variety of microbes that can be transferred to surfaces ("touch microbiome"). These microorganisms can be considered as forensic markers similarly to "touch DNA". With this pilot study, we wanted to evaluate the transferability and persistence of the "touch microbiome" on a surface after the deposition of a fingerprint and its exposure for 30 days at room temperature. Eleven volunteers were enrolled in the study. Skin microbiome samples were collected by swabbing the palm of their hands; additionally, donors were asked to touch a glass microscope slide to deposit their fingerprints, that were then swabbed. Both human and microbial DNA was isolated and quantified. Amelogenin locus and 16 human STRs were amplified, whereas the V4 region of 16 S rRNA gene was sequenced using Illumina MiSeq platform. STR profiles were successfully typed for 5 out of 22 "touch DNA" samples, while a microbiome profile was obtained for 20 out of 22 "touch microbiome" samples. Six skin core microbiome taxa were identified, as well as unique donor characterizing taxa. These unique taxa may have relevance for personal identification studies and may be useful to provide forensic intelligence information also when "touch DNA" fails. Additional future studies including greater datasets, additional time points and a greater number of surfaces may clarify the applicability of "touch microbiome" studies to real forensic contexts. Graphical abstract: Image 1 Highlights: There are some shared taxa among the various donors, defined as the "Core Microbiome". Up to 30 "Donor Characterizing Taxa" per person have been found transferred on the glass surface. "Touch Microbiome" analyses were successful also when standard "Touch DNA" analyses failed. Microbiome analysis can become an additional tool to STR typing for forensic identification.